Предмет: Алгебра,
автор: юляморозко
(√12+√3)²
36/(6√2)²
(√2+√3)-(√2-√3)
Ответы
Автор ответа:
0
(√12+√3)²=(√12)²+2√12√3+(√3)²=
=12+2√36+3=15+2*6=15+12=27
36/(6√2)²=36/(6²√2²)=36/(36*2)=1/2
(√2+√3)-(√2-√3)=√2+√3-√2+√3=2√3
=12+2√36+3=15+2*6=15+12=27
36/(6√2)²=36/(6²√2²)=36/(36*2)=1/2
(√2+√3)-(√2-√3)=√2+√3-√2+√3=2√3
Похожие вопросы
Предмет: Математика,
автор: nikitademidenko08
Предмет: Русский язык,
автор: jiraf225
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: tenpol
Предмет: Математика,
автор: зарина578